Zoonotic Echinococcus granulosus sensu lato genotypes G6 and G7: new insights from the global mitogenome analysis - Biedermann, Anti; Laurimae, Teivi; Anijalg, Liina; Kamenetzky, Laura; V. Soriano, Silvia; Pierangeli, Nora; Saarma, Urmas (Elsevier Sci Ltd, 2025)
Cystic echinococcosis is a severe zoonotic disease caused by different species and genotypes belonging to the Echinococcus granulosus sensu lato (s.l.) complex. Among these, genotypes G6 and G7 are the second most common cause of human cystic echinococcosis. One of the very first steps towards understanding the epidemiology of G6 and G7 is to study their genetic and host diversity, population structure and phylogenetic relationships. For this, we sequenced near-complete mitochondrial genomes (12,850- 12,856 bp) of 72 new G6 and G7 samples from eight countries and six host species, including humans. By adding 103 sequences from previous studies, the total dataset for further analyses comprised of 175 sequences from 20 countries and seven host species. This is the most comprehensive global mitogenome study of Echinococcus granulosus s.l. G6 and G7 to date. The results of this work revealed: (i) a new divergent haplogroup G6b from Mongolia; (ii) the subdivision of genotype G6 into two major haplogroups: G6a (the nominal haplogroup) and G6b (the Mongolian haplogroup); (iii) highly divergent haplotypes of G6 and G7; (iv) the first molecularly confirmed findings of genotype G7 in camel; (v) genotype G7 in sheep - a rare species for G7; (vi) the importance of using long DNA sequences in phylogenetic analysis. (c) 2025 The Author(s). Published by Elsevier Ltd on behalf of Australian Society for Parasitology. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: Cystic echinococcosis; Echinococcus; Genotype G6; Genotype G7; Mitochondrial genome; Zoonoses